(untitled) (AYUSHDHARA, 2015)
The eyes are one of the most sensitive and vulnerable organs in the body. Airborne infections, U. V. rays, pollutants, dust and other particles can land directly on the surface of the eye, causing eye diseases. Arma, is a disease of eye which is characterized by wing like encroachment of the conjunctiva over the cornea2 The causative factors of Arma include exposure to dust, light, Dhooma, Raja, variation in seasons, unhygienic conditions and Asatmya Vihara. Pterygium is common in both developed and developing countries. It affects all age groups and both sexes. It is the common cause of ocular morbidity. It is a major public health concern in the rural areas of developing countries. Arma that is Ptrygium is the disorder in which a thin membrane grown from white of the eye having blood like luster and bluish. It grows over Krishnamandala that is cornea it not only cosmetically disfigures the eye and face but also cause visual disturbance. Arma is managed by Lekhana Anjana when it is in its early stage. Sushruta also explained a surgical procedure for the management of Arma when it is not treated in its early stage and causes complication. The Arma which is in early stage and having thin membrane and curd like coloured can be treated by Netra Kriyakalpa like Anjana. When the wing like growth encroached to the Krishnamandala then it is surgically removed. Here a systematic effort is carried out to establish the efficacy of Guduchyadi Rasakriyanjana in the management of Arma (Pterygium) to add a drop in the ocean of the research.